Product Market Fit Material Serat Rami Sebagai Elemen Material Berkelanjutan Pada Penerapan Desain Furniture - Akbar Khalid, Nahja (Jurusan Seni Rupa ISBI Bandung, 2024)
The proliferation of research and applications of sustainable materials within society has seen a notable increase, leading to constant updates in product segments featuring sustainable materials. This trend is further supported by the growing awareness among the public regarding environmental degradation. Ramie fiber is one such sustainable material serving as an alternative to the dependence on cotton materials in the textile industry. Collaborating with Armonie Ronche from Universitas Padjajaran, the author undertook a series of processes to implement ramie fiber in a furniture product, emphasizing the creation of products with good market value. Over a period of four months, the development process resulted in a living room set where a combination of hemp fiber and teak wood served as the primary elements in the design, globally marketable, and modern Jengki-style furniture.